Multiple metal-metal bond or no bond?: the electronic structure of V2O2 - Hübner, Olaf; Himmel, Hans-Jörg (Angewandte Chemie. International edition, 2017)
Detailed knowledge of the electronic structure of vanadium oxide clusters provides the basis for understanding and tuning their significant catalytic properties. However, already for the simple four-atom V2O2 molecule, there are contradictory reports in the literature regarding the electronic ground state and a possible vanadium-vanadium bond. We herein show through a combination of experimental (matrix isolation) studies and theoretical results that there is a multiple vanadium-vanadium bond in this benchmark vanadium oxide molecule.